PENYULUHAN KESEHATAN SINDROMA METABOLIK PADA LANSIA - Hastuti, Dewi; Rahayu, Erika Putri; Widiyanta, Fauzyah Azzahra; Fedrizon, Fuat; Husein , Habib Husein; Inayah, Hasya Qalbi; Rahmatullah, Ilham Arief; Kholinne, Erica (Jurnal Pengabdian Masyarakat Trimedika, 2024)
The number of elderly people in Indonesia is increasing every year. Currently, the prevalence of metabolic syndrome is also increasing and is especially found among the elderly. Metabolic syndrome has the potential to increase the risk of cardiovascular and kidney disease. Objective: To determine the risk factors, and educate the elderly community regarding metabolic syndrome. Methods: Data was collected with primary data during a visit to the patient's home in Krendang. A 64-year-old woman with complaints of easy fatigue, the results of the physical examination showed blood pressure 170/100 mmHg, waist circumference 112 cm, body mass index 31.5 kg/ m 2, and the results of the supporting examination obtained blood sugar 216 mg/dL and HbA1c 7.5%. The patient has a history of being hospitalized due to fainting due to drinking high sugar drinks 1 year ago. The patient has hypertension, dyslipidemia and diabetes mellitus but does not take medication and checks himself regularly. Conclusion: The results of the study show that the patient does not understand the relationship between the condition of metabolic syndrome and the symptoms experienced as well as the prognosis of his current condition. The student team has educated patients and their families about what metabolic syndrome is, as well as explaining the risk factors that patients have and how to deal with the patient's current condition. Education about awareness of metabolic syndrome is an important part of managing metabolic syndrome in the elderly. Family and local community support can help elderly people with metabolic syndrome undergo treatment.